Neuroticism traits and anxiety symptoms are exhibited in athletes with chronic gastrocnemius myofascial pain syndrome - San-Antolín, M.; Rodríguez-Sanz, D.; Becerro-de-Bengoa-Vallejo, R.; Losa-Iglesias, M. E.; Martínez-Jiménez, E. M.; López-López, D.; Calvo-Lobo, C. (The Journal of Strength and Conditioning Research, 2020)
Common psychological factors, such as anxiety or neurotic personality traits, seem to be associated with pain suffered by athletes. Gastrocnemius muscles present a high prevalence for injury in athletes. These muscles are a region in which myofascial pain syndrome (MPS) frequently develops. Myofascial pain syndrome is characterized by the presence of active myofascial trigger points (MTrPs). This study compared different personality and anxiety symptoms between athletes with and without active MTrPs in the gastrocnemius. A case-control study was conducted in an outpatient clinic. Athletes who performed moderate or vigorous physical activity according to the International Physical Activity Questionnaire were included. Fifty paired-matched athletes with and without active MTrPs in their gastrocnemius muscles (n = 25 in each group) were recruited. Different personality traits (neuroticism, extraversion, psychoticism, and sincerity) and anxiety (state and trait) were evaluated by the Eysenck Personality Questionnaire and State-Trait Anxiety Inventory, respectively. Statistically significant differences (p < 0.01) with an effect size from moderate to large (d = 0.75-1.29) were found for greater neuroticism and sincerity traits in addition to state and trait anxiety in athletes with gastrocnemius MPS compared with healthy controls. In conclusion, athletes with gastrocnemius active MTrPs exhibited higher neuroticism and anxiety symptoms compared with healthy athletes. Mental health may play a key role in athletes with myofascial pain, and future studies should be performed to determine whether neuroticism-related and anxiety-related psychological care could be a key intervention in athletes with gastrocnemius active MTrPs to improve athletic performance and rehabilitation or prevent injuries.